(untitled) (Journal of Global Accounting, 2023)
Recently the Nigerian banking industry, has seen an upsurge on the reliance of contractpersonnel and staff as an intergarl part of human resources. There has been a debate on the effect and implications of this paradigm shift on performance as human capital reporting is yet to be standardized. This study examined the effect of human capital efficiency on the financial performance of quoted commercial banks in Nigeria. A cross[1]sectional analysis of all the banks quoted on the Nigerian Stock Exchange as at 31st December 2018 for a period of 9years (2010 – 2018) was conducted. Expost-facto research design was employed and secondary data were obtained from Nigerian Stock Exchange fact books, annual reports and accounts of the sampled banks. The data obtained were subjected to statistical analysis using Pearson coefficient of correlation, heteroskedasticty, normality test and ordinary least square regression test at 5% level of significance. The results reveal there is a positive and statistically significant relationship between Human Capital Efficiency and financial performance of commercial banks in Nigeria. The researcher recommends the employment of efficient work-force rather than cheap labour in the Nigerian banking system, recognition and inclusion of human capital accounting in the reporting framework of banks and constant effort made to improve human capital efficiency for improved financial performance.